A Bilayer Osteochondral Scaffold with Self‐Assembled Monomeric Collagen Type‐I, Type‐II, and Polymerized Chondroitin Sulfate Promotes Chondrogenic and Osteogenic Differentiation of Mesenchymal Stem Cells. Issue 1 (22nd October 2021) - Rashidi, Narjes; Tamaddon, Maryam; Liu, Chaozong; Brand, David D; Czernuszka, Jan
Abstract : Osteochondral (OC) injuries are suffered by over 40 million patients in Europe alone. Tissue‐engineering approaches may provide a more promising alternative over current treatments by potentially eliminating the need for revision surgery and creating a long‐term substitute. Herein, the goal is to capture the natural biological and mechanical properties of the joint by developing a bilayer scaffold that is novel in two ways: first, a biomimetic bottom‐up approach is used to improve production precision and reduce immunogenicity; monomeric collagen type I and II are self‐assembled to fibrils and then processed to 3D scaffolds. Second, to induce a tissue‐specific response in mesenchymal stem cells (MSCs), polymerized chondroitin sulfate (PCS) is synthesized and grafted to collagen II and hydroxyapatite (HA) is added to collagen I. Incorporation of PCS into collagen II induces a chondrogenic response by upregulation of COL2A1 and ACAN expression, and incorporation of HA into collagen I stimulates osteogenesis and upregulates the expression of COL1A2 and RUNX2. It is remarkable that MSCs give rise to distinct behavior of chondrogenesis and osteogenesis in the two different regions of the bilayer scaffold. This hybrid scaffold of collagen II‐PCS and collagen I‐HA offers a great potential treatment for OC injuries. Abstract : A biomimetic bottom‐up approach is used in the manufacture of a bilayer scaffold. To reduce immunogenicity, monomeric type‐I and type‐II collagen is used. Chondroitin sulphate is polymerized to an 11 times higher molecular weight polymer and grafted to collagen II. Mesenchymal stem cells establish a separate behavior of chondrogenesis and osteogenesis in the different regions of the bilayer.